Inflammatory‐associated myeloid dendritic cells reveals associations between chronic lung diseases and lung cancer - Zhiyu Chen; Jiawei Zou; Fulan Deng; Yaoqing Chu; Lianjiang Tan; Xin Zou; Jie Hao (Wiley, 2024)
ABSTRACT The high risk of patients with chronic lung diseases in developing into lung cancer has been recognised, but the key factors driving such procedure are still barely known. Dendritic cells (DCs) as major antigen presenting cells take part in the immune response in the very upstream, and myeloid DCs regulate the inflammation in pulmonary diseases. In this article, we performed single‐cell RNA sequencing (scRNA‐seq) analyses on DCs from pulmonary diseases. We explore the DC characteristics in chronic lung diseases, lung cancer and healthy control samples. We discover that a special type of DC, which is highly associated with inflammatory, inf‐DC, is abundant in lung cancer samples. Furthermore, we find that there are about 10% patients with chronic lung diseases also has such inf‐DC‐rich pattern. Such proportion is consistent to the fact that about 10% chronic lung disease patients finally developed into cancer. Our findings indicate inf‐DC could be a potential factor to predict the risk of chronic lung disease developing into cancer.